Global legal pluralism : a jurisprudence of law beyond borders / Paul Schiff Berman. - Berman, Paul Schiff (Cambridge University Press, 2012)
We live in a world of legal pluralism, where a single act or actor is potentially regulated by multiple legal or quasi-legal regimes imposed by state, substate, transnational, supranational and nonstate communities. Navigating these spheres of complex overlapping legal authority is confusing and we cannot expect territorial borders to solve all these problems. At the same time, those hoping to create one universal set of legal rules are also likely to be disappointed by the sheer variety of human communities and interests. Instead, we need an alternative jurisprudence, one that seeks to create or preserve spaces for productive interaction among multiple, overlapping legal systems by developing procedural mechanisms, institutions and practices that aim to manage, without eliminating, the legal pluralism we see around us. Global Legal Pluralism provides a broad synthesis across a variety of legal doctrines and academic disciplines and offers a novel conceptualization of law and globalization.